2018
DOI: 10.1155/2018/2941783
|View full text |Cite
|
Sign up to set email alerts
|

Visual Features in Alzheimer’s Disease: From Basic Mechanisms to Clinical Overview

Abstract: Alzheimer's disease (AD) is the leading cause of dementia worldwide. It compromises patients' daily activities owing to progressive cognitive deterioration, which has elevated direct and indirect costs. Although AD has several risk factors, aging is considered the most important. Unfortunately, clinical diagnosis is usually performed at an advanced disease stage when dementia is established, making implementation of successful therapeutic interventions difficult. Current biomarkers tend to be expensive, insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 209 publications
(299 reference statements)
2
37
0
3
Order By: Relevance
“…AD is the most common cause of dementia and is characterized by cognitive decline, caused by the accumulation of extra-and intra-cellular A plaques and hyperphosphorylated tau (40,41). The studies conducted on postmortem brain tissues have revealed excessive chronic inflammation in the plaque area.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…AD is the most common cause of dementia and is characterized by cognitive decline, caused by the accumulation of extra-and intra-cellular A plaques and hyperphosphorylated tau (40,41). The studies conducted on postmortem brain tissues have revealed excessive chronic inflammation in the plaque area.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The most reliable and frequently used biomarkers are elevated levels of Aβ 1−42 , the most toxic form of Aβ, total tau (t-tau), and hyper-phosphorylated tau (p-tau) in the CSF [ 6 ]. Vision-related changes are common in AD [ 7 ] and are summarized in Table 1 . Some of the visual defects are due to degeneration of the visual cortex, while others are attributed to retinal degeneration associated with glaucoma and age-related macular degeneration (AMD) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that chronic elevation of IOP leads to the accumulation of Aβ and p-tau in RGCs, resulting in their loss. This leads to thinning of the RNFL and optic nerve atrophy, ultimately leading to permanent blindness because of the failure to transmit visual stimuli to the brain [ 7 , 8 ]. However, it is difficult to distinguish whether visual defects due to RGC cell loss appear earlier than those due to neuronal loss in the occipital cortex, information critical for the early diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, monitoring of visual functions could identify those living with dementia who are at greater risk of injurious falls and hospitalization that could exacerbate the progression of dementia. Recent reviews have called for more research into the role of visual functions as a less costly and invasive biomarker for the progression or severity of dementia [ 28 , 29 ]. However, the interaction among primary visual function (VA and contrast sensitivity), binocular functions such as stereopsis and horizontal fusional vergence range, and rate of cognitive decline (eg, cognitive test score) in PWD is yet to be evaluated formally.…”
Section: Introductionmentioning
confidence: 99%